ED50 and ED95 of Remimazolam Tosilate Combined with Different Doses of Fentanyl in Elderly Patients for Painless Gastroscopy - Guo Y; Yao Z; Feng Y; Wang D; Wang Y; Lin J (Drug Design, Development and Therapy, 2024)
Yanxia Guo,* Zhihua Yao,* Yan Feng, Dan Wang, Yizheng Wang, Jingyan Lin Department of Anesthesiology, Affiliated Hospital of North Sichuan Medical College, Nanchong, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jingyan Lin, Email linjingyan@nsmc.edu.cnBackground: The novel short-acting benzodiazepine drug, remimazolam tosilate, has been employed for sedation during endoscopic procedures. The optimal loading dosage of remimazolam tosilate in gastroscopy for elderly patients when co-administered with fentanyl remains unclear. Therefore, the primary objective of our research was to ascertain the median effective dose (ED50) and the 95% effective dose (ED95) of remimazolam tosilate in combination with various fentanyl dosages for elderly patients undergoing painless gastroscopy.Methods: Seventy-five patients aged ≥ 65 years and American Society of Anesthesiologists (ASA) class I–III were recruited to undergo elective painless gastroscopy. All patients were randomized assigned to group F1, group F2, and group F3, and were injected intravenously with different doses of fentanyl (0.5 ug/kg, 1 ug/kg, and 1.5 ug/kg) 3 minutes prior to the administration of remimazolam tosilate, respectively. The initial preset dose of remimazolam tosilate was 0.3 mg/kg in group F1, 0.2 mg/kg in group F2, 0.15 mg/kg in group F3. The dose gradient was 0.02 mg/kg per group according to the up-and-down sequential method. Probibt regression model was employed to determine the ED50 and ED95 of remimazolam tosilate.Results: The ED50 of remimazolam tosilate in group F3 was lower than that in group F1 and F2 (0.095 [0.088– 0.108] mg/kg vs 0.162 [0.153– 0.171] mg/kg; 0.258 [0.249– 0.266] mg/kg, p < 0.05). The ED95 of remimazolam tosilate was 0.272 mg/kg (95% CI: 0.264– 0.295 mg/kg) in group F1, 0.175 mg/kg (95% CI: 0.167– 0.200 mg/kg) in group F2 and 0.109 mg/kg (95% CI: 0.101– 0.135 mg/kg) in group F3. The total dosage of remimazolam tosilate decreased gradually with the increasing of fentanyl (p < 0.001). The frequency of injection pain was higher in group F1 compared to groups F2 and F3 (p < 0.05). The patients in group F3 had a lower incidence of hypotension than in groups F1 and F2 (p < 0.05). There was no respiratory depression, intraoperative consciousness, dizziness or delirium in the three groups.Conclusion: The concurrent use of fentanyl reduces the dosage of remimazolam tosilate required for sedative gastroscopy in elderly patients in a dose-dependent manner. Moreover, 1.5 ug/kg fentanyl combined with remimazolam tosilate may reduce the incidence of hypotension and injection pain. These findings should be confirmed in a large-scale study.Keywords: painless gastroscopy, elderly patients, median effective dose, fentanyl, remimazolam tosilate